An evaluation of antibiotic prescribing practices among dentists in Lahore: A cross-sectional study: Antibiotic Prescribing Practices Among Dentists in Lahore - Babar, Palwasha; Virda, Maryam; Haider, Adeel; Alamgir, Wajiha; Afzal, Muhammad; Ahmad Khan, Rana Muhammad (Pakistan Journal of Health Sciences, 2022)
The appropriate use of antibiotics has become a major concern in healthcare. The over prescription and misuse of antibiotics has contributed to antibiotic resistance which has emerged as a major public health issue. Objective: The current study is conducted to investigate the antibiotic use by the dentists and to assess the conformity with evidence-based guidelines. Methods: A convenience sample of 216 dental practitioners were included in the study. A self-structured questionnaire was administered after getting consent from the participants. The questionnaire consisted of demographic details, self-reported usage of antibiotics in different clinical situations and questions exploring the practices regarding the use of antibiotics. Data were analyzed using SPSS version 24.0. Results: 87% of the participants prescribed antibiotics in irreversible pulpitis, 53.7% in dry socket and 78.7% in localized periapical abscess. Regarding their practice of antibiotic prescription, 77.8% participants reported the prescription of antibiotics in addition to the dental treatment for early resolution of the symptoms. 73.2 % reported that they fear the spread of infection if they have not prescribed antibiotics and 66.7% reported the use of antibiotics to defer the patient if the provision of treatment was not possible at the time. 68.9% participants reported that they would resort to some different antibiotic in case of persistent dental pain at the follow-up visit. Conclusions: The study shows indiscriminate and inappropriate use of antibiotics by the dentists. A lack of knowledge among the dental practitioners regarding the evidence-based clinical indications for antibiotics was evident.